THE DETERMINANTS OF CUSTOMER LOYALTY - Resti Hardini; Rahayu Lestari; Elwisam; Kumba Digdowiseiso; Noor Fadhiha Mokhtar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The objective of this study is to identify and analyze the factors that influence customer loyalty in the context of contemporary competitive business. Specifically, we will examine the impact of Brand Satisfaction, Corporate Brand Reputation, and Brand Attachments. The research methodology employed is a Systematic Literature Review (SLR) to investigate noteworthy discoveries in relevant scholarly literature. The results of the SLR analysis indicate that there is a positive correlation between customer satisfaction and the quality of corporate brand reputation with Brand Attachments. This, in turn, leads to an increase in Brand Loyalty. While Corporate Brand Reputation does have a favorable effect on customer perceptions, its influence on Brand Loyalty is comparatively weaker than that of other variables. The results of the multiple linear regression analysis indicate that the combination of these factors exerts a substantial influence on customer loyalty. Hence, it is imperative for companies to prioritize their endeavors towards enhancing customer satisfaction, establishing a favorable brand image, and fostering profound emotional connections with customers in order to achieve maximum levels of loyalty. Ultimately, an extensive understanding of the factors that influence customer loyalty can assist companies in devising more efficient business strategies to sustain and enhance enduring customer relationships.